REGIONAL AND SEASONAL ABUNDANCE OF THE WHITE FISH LACTARWS LACTARIUS (SCHNEIDER) IN THE TIL\WLING GROUNDS OFF BOMBAY — SAURASHTRA COASTS 1957-'63 - Kaikini, A S (Indian Journal of Fisheries, 2011)
The regional and seasonal abundance of Lactarius in the offshore watsrs,heretofere unknowri are studied in detail from Bombay — Saurashtra waters. Ofthe six regions in tiis zone, Kutch ranked highest In Lactarius fishery, both in totalcatch and catch rate followed by Porbunder, Dwaraka, Veraval, Cambay and Bombayregions. The fluctuations in Lactarius fishery for the period 1957-'63 in the6 subareas are discussed in detail. Lactarius is found to concentrate in the 20-45m depth range, 30-35 m being optimum. The distribution pattern through thevarious seasons studied, showed that the depth ranges also change according tothe season. The average catch rate is observed to be highest in the secondquarter of the year. A gradual north-south migration of Lactarius from Kutchcommencing in April culminates by January at Cambay.It seems to move from the 25-40 m ranges in March-April to the 40-70m range in May-June and the reverse movement starts in August-September.